Comparison Between Titanium and Thermally Activated Prostheses in Stapes Surgery - Mila Vasiljević; Klara Dragović; Petra Povalej Bržan; Janez Rebol (Applied Sciences)
This study investigates hearing outcomes of stapedotomy using two different types of prostheses: manually crimped MatriX and thermally activated NiTiBOND. The primary objective was to determine whether the method of prosthesis fixation to the long process of incus influences postoperative results. A retrospective analysis was conducted on 155 patients with otosclerosis; 90 received the NiTiBOND prosthesis and 65 received the MatriX prosthesis. Choice of prosthesis was determined intraoperatively based on position of chorda tympani. If the nerve was located near the incus and the prosthesis fixation site, the surgeon opted for MatriX prosthesis to avoid potential injury from activation of the NiTiBOND. Audiometric evaluations revealed no statistically significant differences in bone conduction thresholds on the first postoperative day (p = 0.275) or at six weeks (p = 0.899), postoperative air-bone gap (p = 0.810), air-bone gap closure (p = 0.489), overclosure (p = 0.436), or bone conduction at 4 kHz (p = 0.324). Chorda tympani nerve injury occurred in 9.2% of cases with MatriX prosthesis and 6.7% with NiTiBOND prosthesis (p = 0.556). Our findings highlight the theoretical and practical significance of comparing both prostheses, demonstrating that NiTiBOND can serve as an alternative in anatomically favorable cases, thereby guiding treatment choices.